2013
DOI: 10.1378/chest.12-1404
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trends in Health-Related Quality of Life in Adults With Cystic Fibrosis

Abstract: In a longitudinal multicenter population of adults with CF, clinical variables such as FEV1, exacerbation frequency, and weight were correlated with related CFQ-R subscales. For the population as a whole, the physical domains of CFQ-R, such as respiratory symptoms, were stable. In contrast, population changes in several psychosocial domains of CFQ-R suggest that differentiating between the physical and the psychosocial trajectories in health among adults with CF is critical in evaluating patient-reported outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 25 publications
5
78
1
Order By: Relevance
“…40 In the present study, there was no evidence of association between BMI and any of the WHOQOL-BREF domain scores, although BMI was a predictor of CFQOL scores. Similar results were demonstrated by Dill et al 41 in a longitudinal study with subject-reported outcomes: nutritional status was associated with CFQ-Revised physical domain scores. Our study demonstrated a significant effect for sex as a predictor of CFQOL scores for the weight and body image domains, but there were no associations with any WHOQOL-BREF scores.…”
Section: Discussionsupporting
confidence: 88%
“…40 In the present study, there was no evidence of association between BMI and any of the WHOQOL-BREF domain scores, although BMI was a predictor of CFQOL scores. Similar results were demonstrated by Dill et al 41 in a longitudinal study with subject-reported outcomes: nutritional status was associated with CFQ-Revised physical domain scores. Our study demonstrated a significant effect for sex as a predictor of CFQOL scores for the weight and body image domains, but there were no associations with any WHOQOL-BREF scores.…”
Section: Discussionsupporting
confidence: 88%
“…S4 in the supplemental material). We employed the CFQ-R because it is a generally accepted framework for discussing health-related quality of life for this disease (79)(80)(81). Whether the ebb and flow of respiratory symptoms in CF are associated with changes in microbial gene transcription is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…Most CF patients 6 years or older, the age group in whom the test is performed routinely in the clinic, are familiar with the test, and with appropriate training accurate measurements are easy to obtain. FEV 1 is considered an appropriate surrogate outcome for CF studies since low FEV 1 values are strongly associated with increased mortality, and decreased quality of life [5][6][7]. 3.…”
Section: Fevmentioning
confidence: 99%
“…Moving forward, it would be preferential to provide data for both absolute and relative changes in FEV 1 for all clinical trials to facilitate the comparison of effect sizes among studies. 6. FEV 1 across the age range Spirometry while easy to perform does require that subjects actively cooperate during testing to ensure both the inspiration to total lung capacity and the forced exhalation reflect their maximal effort.…”
Section: Lack Of Standardized Reportingmentioning
confidence: 99%